INFLUENCE OF PSYCHOLOGICAL FACTORS ON CONSUMER BUYING BEHAVIOR IN CHAIN SUPERMARKETS IN KENYA - Kiboro, Grace Wambui; Omwenga, Dr. Jane; Iravo, Prof. Mike (European Journal of Business and Strategic Management, 2017)
Purpose: The objective of the study was to establish the effect of psychological factors on consumer buying behavior in chain supermarkets in Kenya. Methodology: The target population consisted of 33 chain supermarkets in Kenya. The target population comprised of 634 employees from these supermarkets. Descriptive research design was used for this study. In addition regression and correlation analysis was used to link the relationships between the dependent and the independent variables. Results: The study found out that there was a positive and significant relationship between psychological factors and consumer buying behavior (r=0.29, p=0.000). Recommendation: It was found out that psychological factors have a positive and significant effect on Consumer Buying Behavior. Therefore, the study recommends for chain supermarkets to take care of consumers perceptions (self-confidence, autonomy, defensiveness, adaptability), consumers past experience with the products and the supermarket (learning) value for their money. Additionally they should also take care of consumer needs and wants so as to improve on their revenue performance.